The Phenomenon of Political Humor as a Strategic Tool in Comedy TV Shows in Pakistan - Zoya Aziz; Ayyaz Qadeer; Muhammad Ayub (JSSH, 2023)
Humor, which is primarily designed to amuse, can occasionally be more serious than regular news when utilized with political intent. Numerous studies have demonstrated the importance of humor in politics. Comedy programs are, therefore, the polar opposite of news programs, and attract a larger audience. People who are tired of difficult news discussions prefer fun political programs. It has been established that all types of political comedy programs are the primary source of political news for the public, particularly the younger age. We collected qualitative data of humorous nature for Pakistani perspectives on humor in comedy shows. Online sources have compiled the information about the selected episodes of the Atab Iqbal-hosted program. The obtained data is studied via the prism of Dmitry Chernobrov's strategic comedy theory. This study indicates that the Aftab Iqbal-hosted comedy series serves political aims and promotes a particular political leader and party by criticizing and imitating other parties and leaders.